Development of Demonstration Plots and Assistance of Farmer Group Yellow Soybean Based on Local Wisdom Supporting Food Security in Cilacap District, Central Java, Indonesia - Sri Nuryani Hidayah Utami; Tri Harjaka; Dody Kastono; Jaka Widada; Arif Muliawan; Mulyono Mulyono; Ahmad Romdhon; Angga Prasetya; Maria Gratias; Adi Laksono (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The mentoring and demonstration plot program with the application of technology carried out by the Faculty of Agriculture Universitas Gadjah Mada Team was proven to be able to increase the productivity and quality of soybeans, although some were only applied partially (not completely) from the recommended technology package, this was constrained by many factors in each mentoring area. In the Cilacap area, the demonstration plot results showed a fairly high potential reaching 2.24 tons/ha in Bantarsari, 2.94 and 3.77 tons/ha in Kawunganten, while in Majenang before harvesting soybeans showed good potential with 130-140 pods. per plant, this is of course the potential yield can reach above 3.0 tons/ha, but unfortunately it was affected by the flood due to the broken embankment, so the soybeans were inundated and damaged (rotten) in a relatively short time. The process of technology transfer and adoption that occurred went well, and many farmers gave testimony that this mentoring program was good to be developed and continued, so that under conditions according to the growing season, they would be able to show even better potential.